Perlindungan Hukum Perjanjian Bagi Hasil Petani Garam di Kabupaten Pamekasan dalam Perspektif Hukum Islam dan Hukum Perdata - Syamsi, Achmad Badarus; Qomaro, Galuh Widitya (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
The function of approval in an agreement (contract) is as a statement between the two parties on their respective rights and obligations so that if there are parties whose rights are not fulfilled, they can feel protected and demand these rights. Therefore, it is appropriate that an agreement on a contract must be carried out properly so that it can guarantee the rights of both parties. Madura Island is the best salt field in Indonesia, so there are many contracts between farmers and salt landowners. This article discusses the pattern of revenue sharing between farmers and salt landowners in Pamekasan Regency using the schemes of a half to a third and one fifth to two fifths. These revenue sharing patterns have different rights and obligations. The difference is a bigger obligation to those who get half. The author found that the pattern of production sharing agreements made by farmers and salt landowners in Pamekasan Regency according to the Agreement Law and Islamic Law did not meet the basic principles of agreement, because the agreement was made only verbally and there were no witnesses so that it had an impact on the lack of protection for farmers and the absence of witnesses causes no clarity on the boundaries of the contract.